Quantitative Methods in Comparative Education and Other Disciplines: are they valid? - Steven J. Klees (Universidade Federal do Rio Grande do Sul, 2017)
Comparison is the essence of science and the field of comparative and international education, like many of the social sciences, has been dominated by quantitative methodological approaches. This paper raises fundamental questions about the utility of regression analysis for causal inference. It examines three extensive literatures of applied regression analysis concerned with education policies. The paper concludes that the conditions necessary for regression analysis to yield valid causal inferences are so far from ever being met or approximated that such inferences are never valid. Alternative research methodologies are then briefly discussed.